The Impact of Social Media on Adolescent Identity Formation and Mental Health: Opportunities, Risks, and Policy Implications - Anwar , Mahmood (Yayasan Sinergi Kawula Muda, 2024)
Psychological resilience is a critical factor in mental health and well-being, particularly in the face of increasing global stressors such as the COVID-19 pandemic. This study conducts a comprehensive narrative review to examine the key determinants of resilience, focusing on social support, stress management, cultural influences, and spirituality. A systematic literature search was conducted using Scopus, PubMed, and Google Scholar to identify empirical studies on resilience and its contributing factors. The findings underscore the significant role of social networks in enhancing resilience, demonstrating that individuals with strong support systems experience lower levels of anxiety and depression. Effective stress management techniques, including mindfulness and structured coping strategies, further contribute to resilience by promoting emotional regulation. Additionally, cultural and spiritual factors influence resilience development, with collectivist societies benefiting from community-driven support structures, while individualist cultures rely more on personal coping mechanisms. These results highlight the need for targeted interventions to strengthen resilience across diverse populations. Policymakers must prioritize mental health infrastructure, integrate resilience training into education and workplace settings, and promote digital mental health interventions. Future research should explore longitudinal effects of resilience-building strategies and assess the potential of digital platforms in enhancing psychological resilience. By adopting a multi-dimensional approach, societies can better equip individuals to withstand adversity and improve overall mental well-being.